MENGENAL SLOW LEARNER: TANTANGAN DAN STRATEGI PEMBELAJARAN - Nadia Damayanti Nadia Damayanti; Dina Rahayu Dina Rahayu; Meisya Florencia De.Langgut Meisya Florencia De.Langgut; Joni Tito Kaharap Joni Tito Kaharap; Romiaty Romiaty Romiaty Romiaty (Al-Thifl: Jurnal Pendidikan Anak Usia Dini, 2005)
Understanding the characteristics and needs of slow learner children from an early age is essential in supporting their learning process optimally. Slow learners are part of the group of children with special needs who have slightly below-average intelligence levels and tend to face challenges in cognitive, affective, and socio-emotional aspects. These children are not incapable of learning, but they require more time and tailored approaches that align with their individual conditions and potential. This article uses the Systematic Literature Review (SLR) method, which provides a comprehensive overview of the contributing factors, challenges faced, and effective learning strategies for slow learners. The findings indicate that the causes of this condition include internal factors such as biological and psychological disorders, as well as external factors like inappropriate parenting styles, unresponsive school environments, and social stigma that hinders the child’s development. The challenges faced by slow learners arise not only in school environments but also within families and communities. They often struggle with concentration, abstract thinking, memory retention, and building social relationships. Therefore, individualized, gradual, and consistent learning approaches—both at home and at school—are necessary. Teachers and parents play a central role in supporting the child’s learning process through strategies such as simplified materials, the use of audio-visual media, multisensory approaches, and emotional reinforcement. With the implementation of appropriate strategies, inclusive learning environments, and strong collaboration among educators, parents, and the surrounding community, slow learners can be supported in overcoming their barriers and developing their academic, social, and emotional potential to the fullest.